1998
DOI: 10.1111/j.1540-8159.1998.tb01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Absorbable Suture Technique: Solution to the Growth Problem in Pediatric Pacing with Endocardial Leads

Abstract: STOJANOV, P., FT AL.: Absorbable Suture Technique: Solution to the Growth Problem in Pediatric Pacing with Endocardial Leads. Endocardia! pacing system implantation ims heen performed in 15 chiidren of mean age 37months (ranging from t day to 89 months). Endocardial lead fixation was performed by means of slowly resorhable suture (Dexon) to allow spontaneous lead migration as the child grows. During a mean follow-up period of 61 months (range 17-108 months), none of the patients needed reintervention for corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…However, others have found that the use of a loop placed in the inferior vena cava did not allow the expected lead release over time 12 . In addition, there are reports of recommendations to avoid tie‐downs or using absorbable suture on the anchoring sleeves, with a similar goal of trying to improve lead longevity by allowing migration into the heart as the child grows 7,8,13 . The discrepancy between the choice of available lead lengths and the size of the child at implant may additionally compel the use of excessive lead slack, as the only other option is to coil the excess lead within the pocket 5,14,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others have found that the use of a loop placed in the inferior vena cava did not allow the expected lead release over time 12 . In addition, there are reports of recommendations to avoid tie‐downs or using absorbable suture on the anchoring sleeves, with a similar goal of trying to improve lead longevity by allowing migration into the heart as the child grows 7,8,13 . The discrepancy between the choice of available lead lengths and the size of the child at implant may additionally compel the use of excessive lead slack, as the only other option is to coil the excess lead within the pocket 5,14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…As a means to reduce conductor fractures given the anticipated growth of young patients, it is thought that some redundancy should be left as slack to avoid tension on the pacing leads 3–5 . Other reports recommend the use of an atrial loop to allow for anticipated growth of the child, while still others suggest using absorbable suture to secure the anchor sleeves, in hopes of allowing additional lead to enter the vessel from the pocket with growth 5–8 . This excess lead is thought to extend the interval between lead replacement procedures and allow for patient growth and movement 3–8 .…”
Section: Introductionmentioning
confidence: 99%
“…At initial PM implant, the endocardial pacing lead was inserted by transcutaneous puncture of the subclavian vein and fixed to the subcutaneous tissue with a slowly absorbable ligature 6,7 . Ventricular leads were positioned in the nonsystemic ventricular apex (left ventricle in congenitally corrected transposition of the great arteries, TGA {S, L, L}, and in TGA {S, D, D} after Mustard palliation).…”
Section: Methodsmentioning
confidence: 99%
“…1,5,12 In brief, at initial PM implantation, the endocardial leads were inserted by transcutaneous puncture of the subclavian vein and fixed to the subcutaneous tissue with a slowly absorbable ligature in children and adolescent patients. 13 Ventricular leads were positioned in the nonsystemic ventricular apex. Atrial leads were placed in the right atrial appendage or, in patients with prior cardiac surgery, in the appendage remnant or in the right atrial free wall, and in the left atrial roof in patients with transposition of the great arteries (TGA) S, D, D after Mustard palliation (Fig.…”
Section: Implantation Procedures Follow-upmentioning
confidence: 99%
“…The first PM implantation was at a median age of 4 (range 0. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] years. In these 18 patients, 19 leads (16 ventricular and three atrial) failed after a median follow-up of 10 (3-15) years, and were abandoned and substituted.…”
Section: Patient Populationmentioning
confidence: 99%